Penerapan GRI Standards dalam Penyusunan Laporan Keberlanjutan Tahun 2021 pada Perusahaan Sektor Barang Konsumen Primer - Leonardo Ivan Lasmana; Ririn Breliastiti; Temy Setiawan (JAF (Journal of Accounting and Finance), 2023)
This study aims to analyze, compare, and conclude how consumer non-cyclicals public companies apply the GRI Standards indexes in their sustainability report and what sustainability issues are disclosed by the company. This research was made in addition to fulfilling an assignment from the Governance and Sustainable Business course, as well as to fins out whether consumer non-cyclicals companies disclose topic-specific standards such as. The research method used is descriptive qualitative method which originates from the sustainability reports of 5 listed companies in the consumer non-cyclicals sector in 2021. The five companies have made disclosures on topic-specific standards but some of the companies still does not comply with the GRI Standards. Keywords: GRI, Sustainability Report, Topic-specific Standards